Systemic Inflammation Response Index Predicts Survival Outcomes in Glioblastoma Multiforme Patients Treated with Standard Stupp Protocol. (16th November 2020) - Topkan, Erkan; Kucuk, Ahmet; Ozdemir, Yurday; Mertsoylu, Huseyin; Besen, Ali Ayberk; Sezen, Duygu; Bolukbasi, Yasemin; Pehlivan, Berrin; Selek, Ugur
Abstract : Objectives . We endeavored to retrospectively assess the prognostic merit of pretreatment systemic immune response index (SIRI) in glioblastoma multiforme (GBM) patients who underwent postoperative partial brain radiotherapy (RT) and concurrent plus adjuvant temozolomide (TMZ), namely, the Stupp protocol. Methods . The records of 181 newly diagnosed GBM patients who received the postoperative Stupp protocol were retrospectively analyzed. The SIRI value for each eligible patient was calculated by utilizing the platelet, neutrophil, and lymphocyte measures obtained on the first day of treatment: SIRI = Neutrophils × Monocytes / Lymphocytes . The ideal cutoff values for SIRI connected with the progression-free- (PFS) and overall survival (OS) results were methodically searched through using the receiver operating characteristic (ROC) curve analysis. Primary and secondary end-points constituted the potential OS and PFS distinctions among the SIRI groups, respectively. Results . The ROC curve analysis labeled the ideal SIRI cutoffs at 1.74 (Area under the curve (AUC): 74.9%; sensitivity: 74.2%; specificity: 71.4%) and 1.78 (AUC: 73.6%; sensitivity: 73.1%; specificity: 70.8%) for PFS and OS status, individually. The SIRI cutoff of 1.78 of the OS status was chosen as the common cutoff for the stratification of the study population (Group 1: SIRI ≤ 1.78 (N = 96 ) and SIRI > 1.78 (N = 85 )) and further comparative PFS and OS analyses. Comparisons between the two SIRI cohorts manifested that the SIRI ≤ 1.78 cohort had altogether significantly superior median PFS (16.2 versus 6.6 months; P < 0.001 ) and OS (22.9 versus 12.2 months; P < 0.001 ) than its SIRI > 1.78 counterparts. The results of multivariate Cox regression analyses ratified the independent and significant alliance between a low SIRI and longer PFS (P < 0.001 ) and OS (P < 0.001 ) durations, respectively. Conclusions . Present results firmly counseled the pretreatment SIRI as a novel, sound, and independent predictor of survival outcomes in newly diagnosed GBM patients intended to undergo postoperative Stupp protocol.